2022
DOI: 10.1088/1742-6596/2385/1/012020
|View full text |Cite
|
Sign up to set email alerts
|

A Methodology to identify appropriate refurbishment strategies towards zero energy buildings in a hot and humid climate

Abstract: Significant actions on the building stock are required to reduce energy consumption and emissions from buildings and achieve carbon neutrality by 2050. Consistently, the renovation approach of existing buildings could aim to obtain nearly Zero Energy Buildings or Net Zero Energy Buildings (NZEB). In particular, the solutions to obtain zero-energy buildings vary according to the reference climatic conditions and the technical-constructive characteristics of the buildings undergoing renovation. As part of a rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Thanks to the energy-saving strategies, an optimized PV system was installed. A similar method was also developed in a case study in Panama [68]. Nevertheless, the retrofit was performed after the photovoltaic system installation because of the necessity of achieving an NZEB.…”
Section: Use Of Systems or Equipment With Greater Efficiencymentioning
confidence: 99%
“…Thanks to the energy-saving strategies, an optimized PV system was installed. A similar method was also developed in a case study in Panama [68]. Nevertheless, the retrofit was performed after the photovoltaic system installation because of the necessity of achieving an NZEB.…”
Section: Use Of Systems or Equipment With Greater Efficiencymentioning
confidence: 99%
“…Only two numerical studies exist in Panama regarding the retrofitting of buildings via dynamic simulations at the building scale [79] and at urbanization scale [80], using the optimization technique contrasting total construction cost with electricity consumption. At the building scale, preliminary technological solutions to adapt existing buildings in Panama into zero energy buildings were identified by employing sensitivity and optimization analyses combined with total construction costs.…”
Section: Evidence Of Buildings Retrofit Toward Nzeb In Panamamentioning
confidence: 99%
“…Results showed that the critical variables influencing electricity consumption are cooling set point, window-to-wall ratio (WWR), and cooling operation schedule. The most appropriate solutions were: (i) When WWR near 30% is recommended, lower cooling set points can be used (near 24°C); (ii) when a higher WWR than 30% is recommended, a higher cooling set point is required (near 27°C) with high CoP values; and (iii) either the appliances increase efficiency, or the occupants' usage needs to change [79]. At the urbanization scale, after applying optimization techniques within the retrofit category related to the building envelope and occupant behavior, a 60% electricity reduction was attained while reducing the renewable energy generation capacity to 10%.…”
Section: Evidence Of Buildings Retrofit Toward Nzeb In Panamamentioning
confidence: 99%
See 2 more Smart Citations